The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.toxlet.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Amine modification of nonporous silica nanoparticles reduces inflammatory response following intratracheal instillation in murine lungs

Abstract: Amorphous silica nanoparticles (NPs) possess unique material properties that make them ideal for many different applications. However, the impact of these materials on human and environmental health needs to be established. We investigated nonporous silica NPs both bare and modified with amine functional groups (3-aminopropyltriethoxysilane (APTES)) in order to evaluate the effect of surface chemistry on biocompatibility. In vitro data showed there to be little to no cytotoxicity in a human lung cancer epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 55 publications
6
36
0
Order By: Relevance
“…It was reported that SiO 2 NPs modified with amine functional groups induced less serious lung inflammation and possessed better biocompatibility. 38 Lu et al found that amino and carboxyl surface modification mitigated the hepatic toxicity of SiO 2 NPs. 39 However, there is a lack of more meticulous and systemic studies about the effects of surface modification on the toxicity of SiO 2 NPs.…”
mentioning
confidence: 99%
“…It was reported that SiO 2 NPs modified with amine functional groups induced less serious lung inflammation and possessed better biocompatibility. 38 Lu et al found that amino and carboxyl surface modification mitigated the hepatic toxicity of SiO 2 NPs. 39 However, there is a lack of more meticulous and systemic studies about the effects of surface modification on the toxicity of SiO 2 NPs.…”
mentioning
confidence: 99%
“…The polydispersity index (PDI) and particle-size diameters of the amine-modified SiO 2 NPs are determined and listed in Figure 6a-d. All amine-modified SiO 2 NPs formed aggregates or cluster at pH 7 and their sizes were altered by changing the pH of aqueous solutions either in acidic or alkaline aqueous solutions (Figure 6a-d). The amine-modified silica nanomaterials tend to form interparticle network and consequently gelation, which increased with increasing the amine contents [35][36][37][38][39]. The increasing of the particle sizes of SiO 2 -10-10 NPs (Figure 5d) more than other amine-modified SiO 2 NPs agrees with the previous works [35][36][37][38][39] and elucidates the increasing of amine contents on its surfaces as confirmed from FTIR and TGA analysis ( Figures 1a-d and 2a-d, respectively).…”
Section: Effect Of Ph On the Surface And Particle Sizes Of Sio 2 Npsmentioning
confidence: 99%
“…One possible reason for the discrepancy in the findings regarding the role of amine‐modifications of the silica surface for toxicity might stem from differences in the quantitative coverage by the functional groups. It is assumed that replacement of reactive silanol groups by amino groups prevents their detrimental interaction with cells . However, it has not been determined yet, how much of the silica surface needs to be covered by amino groups to suppress toxicity.…”
Section: Introductionmentioning
confidence: 99%